Electrospun N‐Substituted Polyurethane Membranes with Self‐Healing Ability for Self‐Cleaning and Oil/Water Separation. Issue 3 (10th December 2015) - Fang, Wenyuan; Liu, Libin; Li, Ting; Dang, Zhao; Qiao, Congde; Xu, Jinku; Wang, Yanyan
Abstract: Membranes with special functionalities, such as self‐cleaning, especially those for oil/water separation, have attracted much attention due to their wide applications. However, they are difficult to recycle and reuse after being damaged. Herein, we put forward a new N‐substituted polyurethane membrane concept with self‐healing ability to address this challenge. The membrane obtained by electrospinning has a self‐cleaning surface with an excellent self‐healing ability. Importantly, by tuning the membrane composition, the membrane exhibits different wettability for effective separation of oil/water mixtures and water‐in‐oil emulsions, whilst still displaying a self‐healing ability and durability against damage. To the best of our knowledge, this is the first report to demonstrate a self‐healing membrane for oil/water separation, which provides the fundamental research for the development of advanced oil/water separation materials. Abstract : A clean sweep ! The as‐prepared membrane has a self‐cleaning surface with an excellent self‐healing ability. Importantly, by tuning the membrane composition, the membranes not only exhibit different wettability for effective separation of oil/water mixtures and water‐in‐oil emulsion but also still display a self‐healing ability (see scheme).